2018
DOI: 10.31083/j.jmcm.2018.04.4221
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic to mesenchymal fate switching of neuroblastoma occurs spontaneously in vivo resulting in differential tumorigenic potential

Abstract: Neuroblastoma is a pediatric tumor that originates from cells of the adrenergic lineage. Here we investigated the balance between differentiation and dedifferentiation in relation to tumor-engraftment potential in preclinical mouse models. We analyzed intratumoral heterogeneity through comparison of marker expression of normal adrenergic development versus tumor marker expression, which showed the presence of sympathoadrenal as well as mesenchymal subtypes of neuroblastomas cells. Subsequently, we evaluated lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…Using single-cell sequencing, we could facilitate virtual microdissection of malignant cells and microenvironmental heterogeneity within and between tumors. In particular, among malignant populations, we detected the expression of genes related to mesenchymal/neural crest cell and adrenergic/noradrenergic neuroblastoma cells, consistent with previous reports 7,8,36,37 . Notably however, we found that some high-risk tumors display an additional transitional state with gene expression characteristics associated with aggressive disease, rapid proliferation and metastasis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Using single-cell sequencing, we could facilitate virtual microdissection of malignant cells and microenvironmental heterogeneity within and between tumors. In particular, among malignant populations, we detected the expression of genes related to mesenchymal/neural crest cell and adrenergic/noradrenergic neuroblastoma cells, consistent with previous reports 7,8,36,37 . Notably however, we found that some high-risk tumors display an additional transitional state with gene expression characteristics associated with aggressive disease, rapid proliferation and metastasis.…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies have speculated that adrenergic/noradrenergic cells transdifferentiate to mesenchymal/neural crest cells and vice versa 7,8,36,37,41 . This theory was primarily based on spontaneous state polarization of isogenic pairs of cells and forced overexpression experiments using strong lineage associated transcription factors to reprogram cell phenotype such as PHOX2B, PRRX1, ASCL1 and NOTCH3 7,8,36,41 .…”
Section: Pntsmentioning
confidence: 99%
“…Single-cell subclones established from NB cell lines could repopulate both cellstates in vitro, indicating reversible dynamic transitions. Such spontaneous stochastic bidirectional interconversion was also seen in vivo (Lecca et al, 2018;Thirant et al, 2023;. Therefore, analogous to the well-studied phenomenon of epithelial-mesenchymal transition (EMT) and its reverse mesenchymal-epithelial transition (MET) (Kahlert et al, 2017;Lourenco et al, 2020;Pastushenko and Blanpain, 2019), neuroblastoma displays phenotypic transitions between the NOR and MES phenotypes -noradrenergic-mesenchymal transition (NMT) and mesenchymal-noradrenergic transition (MNT) (Figure 1).…”
Section: Introductionmentioning
confidence: 77%
“…Transdifferentiation between these cell identities is associated with cellular plasticity ( van Groningen et al, 2017 ; van Groningen et al, 2019 ). The differentiation state of cells within a tumor and the cross-talk between the different subtypes is relevant in drug resistance and relapse ( Yan et al, 2011 ; Lecca et al, 2018 ). The differential responses to retinoic acid treatment and withdrawal we observed may also reflect these divergent differentiation states.…”
Section: Discussionmentioning
confidence: 99%